Differences in Elastin and Collagen Levels in the Levator Ani Muscle of Primiparous and Multiparous Normal Postpartum Women - Rada, Annisa Astika; Rahajeng, Rahajeng; Dwijayasa, Pande Made; Gunawan, Didik Agus (Faculty of Medicine, Universitas Padjadjaran, 2024)
The levator ani, comprising the pubococcygeus, puborectalis, and iliococcygeus muscles, is crucial for supporting pelvic organs, maintaining continence, and ensuring pelvic stability. Weaknesses in these muscles or ligaments can lead to pelvic organ prolapse (POP), a condition where the pelvic organs descend and protrude through the vaginal introitus. Collagen and elastin, the key constituents of the extracellular matrix in the levator ani muscle, play a significant role in maintaining its structural integrity and can be influenced by parity. This study aimed to determine the differences in elastin and collagen levels of the levator ani muscle of primiparous and multiparous patients. This was an observational analytical study on 18 postpartum female patients consisting of 9 primiparous and 9 multiparous in January-March 2023. Samples were levator ani muscle biopsies from perineal lacerations of at least grade II from the inpatient Obgyn Department of the Faculty of Medicine, Universitas Brawijaya. Examination was done using the immunohistochemical method. Results showed that the percentage of histological area secreting elastin and collagen was higher in the primiparous group than multiparous, thus the levels were higher (p<0.001; p=0.001; p<0.05). In conclusion, elastin and collagen levels were lower in multiparous women compared to primiparous women. Future studies can evaluate factors affecting the decline in elastin and collagen in multiparous women using a larger sample size.